2021
DOI: 10.1186/s12938-021-00929-w
|View full text |Cite
|
Sign up to set email alerts
|

Gait training with a wearable curara® robot for cerebellar ataxia: a single-arm study

Abstract: Background Ataxic gait is one of the most common and disabling symptoms in people with degenerative cerebellar ataxia. Intensive and well-coordinated inpatient rehabilitation improves ataxic gait. In addition to therapist-assisted gait training, robot-assisted gait training has been used for several neurological disorders; however, only a small number of trials have been conducted for degenerative cerebellar ataxia. We aimed to validate the rehabilitative effects of a wearable “curara®” robot d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Although our findings did not reach statistical significance, it is worth noting that a substantial number of subjects with cerebellar ataxia (swCA) who improved the most in sLLE ML , 33.33%, specifically (Table 4), had poorer gait quality at baseline, according to their SARA GAIT scores. This observation is consistent with existing literature [20,65] reporting the effectiveness of rehabilitation training in swCA in more severely disabled swCA, regardless of disease duration, implying that individuals with swCA may be able to improve their dynamic trunk stability despite ongoing degeneration. Notably, unlike other studies investigating the effects of rehabilitation on gait parameters [19,20,24], gait speed did not improve in our sample, suggesting that sLLE may capture the effects of rehabilitation regardless of gait speed.…”
Section: Discussionsupporting
confidence: 92%
“…Although our findings did not reach statistical significance, it is worth noting that a substantial number of subjects with cerebellar ataxia (swCA) who improved the most in sLLE ML , 33.33%, specifically (Table 4), had poorer gait quality at baseline, according to their SARA GAIT scores. This observation is consistent with existing literature [20,65] reporting the effectiveness of rehabilitation training in swCA in more severely disabled swCA, regardless of disease duration, implying that individuals with swCA may be able to improve their dynamic trunk stability despite ongoing degeneration. Notably, unlike other studies investigating the effects of rehabilitation on gait parameters [19,20,24], gait speed did not improve in our sample, suggesting that sLLE may capture the effects of rehabilitation regardless of gait speed.…”
Section: Discussionsupporting
confidence: 92%
“…They found that these patients could walk more smoothly with an increased harmonic ratio while walking with the wearable robot system than without the system. In addition, other studies have demonstrated improvements in gait function and postural balance after weeks of RAGT with the wearable robot system in patients with spinocerebellar ataxia [ 29 , 30 ]. These findings suggest the potential benefit of over-ground RAGT for patients with ataxia.…”
Section: Discussionmentioning
confidence: 99%
“…We started clinical research in 2017 for the practical application of a wearable rehabilitation robot, “curara®”. We have examined the effect of the device in patients with spinocerebellar degeneration [ 13 , 14 ] and stroke [ 15 ]. We have shown that the use of the device improves walking speed, stride length, walking rate, and asymmetry in stroke patients temporarily [ 15 ], but we have not yet clarified its rehabilitative effect on gait training.…”
Section: Introductionmentioning
confidence: 99%